The Influence of Appropriateness of Work Roles, Compensation, and Quality of Work Life on Employee Job Satisfaction Through Work Involvement as Intervening Variables at the Department of Public Works and Spatial Planning in Jepara Regency - Agung Veriyanta; Sunarno; Sutono (Indonesian Journal of Business Analytics, 2023)
This study aims to analyze the effect of work role fit, compensation and quality of work life on job satisfaction of the employees of the Public Works and Spatial Planning Department of Jepara Regency with job involvement as an intervening variable. The research population was all employees of the Public Works and Spatial Planning Department of Jepara Regency, amounting to 239 people. Sampling taken in this study using stratified random sampling as many as 150 employees. The instrument test uses validity and reliability tests. The analysis technique uses the SEM (Structural Equation Modeling) application program AMOS. The results showed that the work role fit, compensation, and quality of work life had a positive and significant effect on job involvement. Suitability of work roles, compensation, quality of work life and job involvement affect employee job satisfaction. Work role fit, compensation, and quality of work life affect employee job satisfaction through work involvement as an intervening variable.